Variation in the Pathogenicity of 20 Algerian Isolates of «Pyrenophora graminea» Ito e Kur. on Nine Barley («Hordeum vulgare» L.) Varieties - Bembelkacem, Abdelkader; Amri, Ahmed; Boulif, Mohammed; Ceccarelli, Salvatore (Phytopathologia Mediterranea, 2000)
Pathogenic variability in isolates of Pyrenophora graminea, the casual organism of leaf stripe of barley(Hordeum vulgare L.), collected from different barley-growing areas of Algeria was investigated by artificially inoculating19 isolates from Algeria and 1 from Syria on nine barley varieties. The isolates were found to exhibit variationand physiological specialization and variation to particular barley varieties. All isolates had different virulence spectraand could be divided into 12 homogeneous groups. The most virulent group was composed of six isolates each,virulent on six of the nine barley varieties. The isolate from Syria was the least virulent. The results demonstratedthat the population of P. graminea was highly variable at country level and within regions. The barley varieties useddiffered in the genetic factors making them resistant to the pathogen and in this way it was possible to discriminateamong the isolates. Varieties NK 1272 and M 23 were resistant to all isolates. This set of genotypes can be used asdifferentials in the future and as sources of resistance for any geographic and sequential gene deployment strategy.